Distortions to Agricultural Incentives in China and Southeast Asia - Anderson, Kym; Martin, Will (World Bank, Washington, DC, 2017)
This chapter begins with a brief summary of economic growth and structural changes in the region since the 1950s and of agricultural and other economic policies as they affected agriculture before and after the various reforms, and in several cases fundamental regime changes, of the past half-century. It then summarizes new estimates of the nominal rate of assistance (NRA) and the relative rate of assistance (RRA) to farmers delivered by national farm and nonfarm policies over the past several decades (depending on data availability), and of those policies' impacts on consumer prices of farm products. Both farmer assistance and consumer taxation is negative in periods where there is an anti-agricultural, pro-urban consumer bias in a country's policy regime. The final sections summarize what the author have learned and draw out implications of the findings, including for poverty and inequality and for possible future directions of policies affecting agricultural incentives in this part of Asia.